2020
DOI: 10.1177/0972150920975116
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Coronavirus Research Output: A Bibliometric Analysis

Abstract: The aim of this article is to examine the bibliometric analysis of global publication output on coronavirus, as covered in Web of Science during the period from 2000 to 2019. A total of 10,861 documents were found during a 20-year period spanning from 2000 to 2019 published in the ISI Web of Science. The study analyses annual productivity, most productive source titles, prolific countries, eminent institutions, linguistic analysis and productivity of authors and their contribution in the subject area. The find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…All 17 bibliometric analyses were published in 2020 and included between 641 and 15,207 primary studies ( Table 4 ). Two included articles from India ( 26 , 38 ), one from Spain ( 34 ), one from Turkey ( 27 ), two from Israel ( 9 , 31 ), and the remaining 7 reports were from China ( Appendix , Supplementary Table 4 ). All the 13 included articles were published in journals with IF from 0 to 5.993 ( Appendix , Supplementary Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All 17 bibliometric analyses were published in 2020 and included between 641 and 15,207 primary studies ( Table 4 ). Two included articles from India ( 26 , 38 ), one from Spain ( 34 ), one from Turkey ( 27 ), two from Israel ( 9 , 31 ), and the remaining 7 reports were from China ( Appendix , Supplementary Table 4 ). All the 13 included articles were published in journals with IF from 0 to 5.993 ( Appendix , Supplementary Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 17 (9,11,26,27,(30)(31)(32)(33)(34)(35)(36)(37)(38) CoV-related bibliometric analyses from 13 articles were included, of which one study (27) conducted five bibliometric analyses. All 17 bibliometric analyses were published in 2020 and included between 641 and 15,207 primary studies (Table 4).…”
Section: Study Characteristics Of Published Bibliometric Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…A pioneering empirical study on the consequences of this pandemic for firms was carried out by Kraus et al [7], with the results being obtained from firms based in Germany, Austria, Italy, Switzerland, and Liechtenstein, through semi-structured interviews (27). The researchers concluded that family firms showed a decisive and quick response capacity to the rapid changes occurring in the course of this pandemic, namely by implementing precautionary measures to lessen contagion and safeguard their business activities for the future as well as possible.…”
Section: Consequences For Sme Business and Managementmentioning
confidence: 99%
“…It is therefore important to determine the efficacy of government measures proposed to ensure firms' survival during this lockdown [4,26]. Lastly, Ali, Hakak, and Amin [27] have also advocated that it is essential to understand all the implications of this pandemic from various perspectives. In addition, the same authors noticed in their study that the business and management area is not in the top ten topics of research on COVID-19.…”
Section: Introductionmentioning
confidence: 99%